2009
DOI: 10.1177/1063426609334280
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health and Special Education Services at School Entry for Children Who Were Involved With the Child Welfare System as Infants

Abstract: This study examines mental health and special education needs and service use at school entry among children involved in maltreatment investigations as infants. Data are from the National Survey of Child and Adolescent Well-Being, a national probability study of 5,501 children investigated for maltreatment. The study sample comprised 959 children who were infants at baseline and 5 to 6 years old at the last follow-up. Half had behavioral or cognitive needs at entry to school. About a quarter received outpatien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 37 publications
2
31
0
Order By: Relevance
“…An additional important finding of this research is the striking amount of unmet need for special education and support services in the CW population, which is consistent with other studies (Ringeisen et al 2009). Forty-one percent of children in this sample were characterized as moderate or severe on educational indices, and 61% demonstrated moderate or severe scores on behavioral indices.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…An additional important finding of this research is the striking amount of unmet need for special education and support services in the CW population, which is consistent with other studies (Ringeisen et al 2009). Forty-one percent of children in this sample were characterized as moderate or severe on educational indices, and 61% demonstrated moderate or severe scores on behavioral indices.…”
Section: Discussionsupporting
confidence: 86%
“…Previous research using a national probability sample of children in CW shows that this group is at significant risk for developmental and cognitive delay (Crozier and Barth 2005;Stahmer et al 2005;Landsverk et al 1996a). Speech and language difficulty (Coster and Cicchetti 1993;Ringeisen et al 2009) as well as socio-behavioral and mental health problems also characterizes this group (Landsverk and Garland 1999;Landsverk et al 2002;Landsverk et al 1996b;Leslie et al 2004;Ringeisen et al 2009;Urquiza et al 1994). Moreover, from an educational perspective, maltreated children have a higher likelihood of experiencing school difficulties, including reading problems and decreased achievement than children from matched SES backgrounds and often suffer negative educational outcomes over and above those associated with poverty alone (Leiter and Johnsen 1994;Delaney-Black et al 2002;Veltman and Browne 2001).…”
Section: Characteristics Of Children In Cwmentioning
confidence: 92%
“…These findings are consistent with historical findings that indicate disabilities are twice as prevalent among a maltreated sample as among a nonmaltreated sample (Sullivan & Knutson, 1998). Ringeisen et al (2009) examined child cognitive delay among children who had been involved with a CPS investigation at less than 1 year of age and were now entering school. They utilized NSCAW standardized measures of intelligence and language to identify delays as two or more standard deviations below the mean.…”
Section: Disability Prevalence In Child Welfare Samplessupporting
confidence: 90%
“…In almost all cases, the representation of cognitive need is measured on an ''existence'' scale (absence or presence). Ringeisen et al (2009) found that 32% of children 5-to 6-years postinvestigation demonstrated clinically significant behavioral problems and impairments in daily-living skills. Stahmer et al (2009) measured behavior using the Child Behavior Checklist (CBCL) at the scale level and found the average score to be 53.93 (11.11).…”
Section: Disability Prevalence In Child Welfare Samplesmentioning
confidence: 98%
See 1 more Smart Citation